2009
DOI: 10.3758/mc.37.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Does feigning amnesia impair subsequent recall?

Abstract: Defendants who are accused of serious crimes sometimes feign amnesia to evade criminal responsibility. Previous research has suggested that feigning amnesia might impair subsequent recall. In two experiments, participants read and heard a story about a central character, described as "you," who was responsible for the death of either a puppy (Experiment 1) or a friend (Experiment 2). On free and cued recall tests immediately after the story, participants who had feigned amnesia recalled less than did participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 17 publications
5
51
3
Order By: Relevance
“…Session 1 condition manipulations have proven successful in prior studies (e.g., McWilliams et al, ; Sun et al, ). Analyses thus concerned Session 2 scores only.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Session 1 condition manipulations have proven successful in prior studies (e.g., McWilliams et al, ; Sun et al, ). Analyses thus concerned Session 2 scores only.…”
Section: Resultsmentioning
confidence: 92%
“…Of interest, being in the Commission condition predicted decreased accuracy and increased omission errors as well. In their simulated amnesia study, Sun et al () reported that in their No Rehearsal and Omission conditions recall was significantly worse than in their Truth condition. Sun et al concluded that the effect was due to differential rehearsal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have investigated the negative consequences of feigning amnesia on the actual memory for a crime (See Table 1; Bylin, 2002;Bylin & Christianson, 2002;Christianson & Bylin 1999;Sun, Punjabi, Greenberg, & Seamon, 2009;. The typical procedure to explore the memory-undermining effect of feigning crime-related amnesia is as follows: To begin with, individuals are usually exposed to a written/narrative script about a crime.…”
Section: The Memory-undermining Effect Of Feigning Amnesiamentioning
confidence: 99%